P‐108: Positive Aging Mechanisms for High‐efficiency Blue Quantum Dot Light‐emitting Diodes. Issue 1 (30th May 2018) - Ding, Wen-Cheng; Chen, Chia-Hsun; Huang, Li-Jen; Kuo, Ming-Cheng; Kuo, Ya-Pei; Chen, Peng-Yu; Lu, Hsueh-Hsing; Lin, Yu-Hsin; Tierce, Nathan; Bardeen, Christopher J.; Lee, Jiun-Haw
Abstract : Voltage reduction (2.4 V at 2 mA/cm 2 ) and efficiency improvement (7‐times) were demonstrated in blue QLEDs by positive aging process, which came from (1) improvement of carrier injection at ZnO/QD interface and/or carrier transport in QD layer, and (2) enhancement of PLQY of QD emissive layer.